Seroprevalence of human cystic echinococcosis in individuals occupationally exposed to Canidae in Central Iran: A case-control study - Seyed Hossein Hejazi; Reza Kalantari; Seyed Mahmoud Mousavi; Marzieh Safari; Zahra Ghayour; Zary Nokhodian; Mahsa Esmaeilifallah (Food and Waterborne Parasitology)
Echinococcus granulosus is a widespread zoonotic tapeworm that causes human cystic echinococcosis. Human CE, transmitted via dogs or Canidae feces, poses a public health challenge and exemplifies the One Health Theory. This survey was conducted to determine the seroprevalence of CE in individuals occupationally exposed (IOE) to dogs, livestock wool, and contaminated soil due to egg shedding from dogs/Canidae in industrial slaughterhouses and livestock fields, compared to a healthy control group in Isfahan province, central Iran. In a case-control study, 401 sera from IOE, including slaughterhouse workers, animal husbandry unit workers, wool industry workers, farm workers, livestock farmers, butchers, and veterinarians in the case group, were matched with 401 archived samples from the general population. All 802 samples were tested for echinococcosis IgG using ELISA. Out of 802 sera, 7 (0.9 %) tested positive for Echinococcus IgG. The seroprevalence in the IOE and control groups was 1.2 % (5/401) and 0.5 % (2/401), respectively. Although there was a 2.5-fold estimated risk of CE in IOE compared to the control group, this was not statistically significant. Based on the current study's findings, the overall seroprevalence of CE in the Isfahan area is similar to that of other regions in Iran.